Demographic Characteristics, Laboratory Findings, Radiological Features, and Outcomes of Patients with COVID-19: A Single-center Descriptive Study - Rajabto, Wulyo; Pramita, Prasna; Tadjoedin, Hilman; Gaol, Donnie Lumban; Hardini, R.A. Sri; Tarigan, Nirmala Purbasari; Chandika, Vitya; Manangka, Rumuat Semuel Wullul; Pyrhadistya, Maria (Open Access Macedonian Journal of Medical Sciences, 2023)
The coronavirus disease 2019 (COVID-19) has resulted in a global crisis, affecting hundreds of millions of individuals, with Indonesia reporting a significant increase in cases in July 2021. Therefore, this study aims to describe the clinical, laboratory findings, radiological features, and outcomes of hospitalized patients with COVID-19. This retrospective study was carried out using 606 hospitalized COVID-19 patients who were admitted to the isolation ward in a Hospital in South Jakarta, Indonesia, from January 1 to April 30, 2021. The median age of the patients was 45 years, 55.6% were male, and 85.5% had non-severe diseases, with the most common presenting symptoms being fever, cough, and gastrointestinal symptoms. Patients with severe disease were significantly older (P<0.001), more likely to have hypertension (P<0.05) and diabetes (P<0.001), have an increased CRP (P<0.001), high ferritin (P<0.001), and increased d-dimer (P<0.001). Compared to patients who survived, patients who had died were older (P<0.001), had hypertension (P=0.013), increased CRP (P<0.001), high ferritin (P=0.002), and increased d-dimer (P=0.006). These results showed that older age, comorbidities, and a higher level of CRP, ferritin, and d-dimer increased the risk of severe disease and poor clinical outcomes in hospitalized COVID-19 patients.